Enhancement of proton conductivity of crosslinked poly(vinyl alcohol) through introduction of zeolitic imidazolate framework-8 and imidazole. (26th October 2021) - Tasarin, Sawanya; Panawong, Chonnakarn; Sumranjit, Jitapa; Budsombat, Surangkhana
Abstract: Proton exchange membranes from crosslinked poly(vinyl alcohol) using sulfosuccinic acid (SSA) and glutaraldehyde as double crosslinking agents were reported. The effect of SSA content on water uptake and proton conductivity was investigated. The most promising membrane was then formed into composites with zeolitic imidazolate framework-8 (ZIF-8). ZIF-8 was synthesized, and confirmed by Fourier transform infrared spectroscopy, X-ray diffraction analysis, and transmission electron microscopy. The effect of ZIF-8 loading (0–10%) on membrane properties was firstly reported. Relatively good dispersion of ZIF-8 nanoparticles was observed for composites with %loadings up to 5%. The enhancements in proton conductivity and mechanical strength were observed upon ZIF-8 addition, and the optimum loading was 5%. In an attempt to improve proton conductivity at low relative humidity, the composite was further doped with imidazole. Proton conductivity increased with increasing imidazole content and temperature, and reached a maximum of 2.3 × 10 −4 S/cm at 80 °C under non-humidified condition. Graphical abstract: Image 1 Highlights: Crosslinked PVA and ZIF-8 composite membranes were prepared. ZIF-8 enhanced proton conductivity and mechanical strength. ZIF-8 composites were further doped with imidazole for uses under low RH. Proton conductivity increased with increasing imidazole content and temperature.